2006
DOI: 10.1021/jp0628582
|View full text |Cite
|
Sign up to set email alerts
|

Study of Adsorption and Penetration of E2(279−298) Peptide into Langmuir Phospholipid Monolayers

Abstract: The peptide corresponding to the sequence (279-298) of the Hepatitis G virus (HGV/GBV-C) E2 protein was synthesized, and surface activity measurements, pi-A compression isotherms, and penetration of E2(279-298) into phospholipid monolayers spread at the air-water interface were carried out on water and phosphate buffer subphases. The results obtained indicated that the pure E2(279-298) Langmuir monolayer exhibited a looser packing on saline-buffered than on pure water subphase and suggest that the increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
4
18
0
Order By: Relevance
“…34 mN/m similar, for example, to that obtained by Miñones et al [31] (33 mN/m) for another phospholipid mixture (DMPC:DMPG). Thus, we conclude that the peptide adsorption is mostly caused by the negative charge of DMPG molecules when compared with the behavior displayed by pure DPPC monolayer, for which no peptide adsorption was observed [39].…”
Section: Isothermssupporting
confidence: 88%
See 1 more Smart Citation
“…34 mN/m similar, for example, to that obtained by Miñones et al [31] (33 mN/m) for another phospholipid mixture (DMPC:DMPG). Thus, we conclude that the peptide adsorption is mostly caused by the negative charge of DMPG molecules when compared with the behavior displayed by pure DPPC monolayer, for which no peptide adsorption was observed [39].…”
Section: Isothermssupporting
confidence: 88%
“…They have been extensively studied by a broad range of techniques, leading to detailed information on both structure and molecular orientation of their constituents [28][29][30]. Studies on mixed monolayers by air-water interface isotherms provide information about the interactions, miscibility, and stability of the monolayer [10,31]. Complementary information is obtained from images of Langmuir-Blodgett films, by atomic force microscopy (AFM) measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid mixing and red blood cell haemolysis studies identified the 279–298 peptide as more able to disrupt lipid bilayers, suggesting that it is more likely to be an internal fusion peptide than the 267–284 peptide [58,60]. Additional physiochemical analyses with Langmuir phospholipid monolayers demonstrate that the 279–298 peptide modifies the surface behaviour of phospholipid monolayers, further suggesting that this peptide may be involved in membrane fusion [61]. Of note, the 279–298 peptide is unstructured in aqueous solution, but forms an amphipathic helical structure in the presence of lipids and model membranes, further supporting a role in virus-cell fusion [62].…”
Section: Gb Virus C Envelope Glycoproteinsmentioning
confidence: 99%
“…Air/Liquid Interface Measurements-The experiments in the absence of lipid at the air/liquid interface, prior to lipid/liquid interface, allow determination of the following: (i) the amphiphilic properties of the protein; (ii) the concentration at which the protein saturates the lipid-free interface (16) in a way to minimize the protein aggregation that could result from a high protein concentration; and (iii) the concentration of the protein (13). Underlined residues indicate the start (N terminus column) or end (C terminus column) residue of the repeat from the alignment of Koenig and Kunkel (57).…”
Section: Dys R11-15/langmuir Experimentsmentioning
confidence: 99%